Von Müttern und anderen Weiblichkeitsentwürfen –Thomas Manns frühe Frauenfiguren im Spannungsverhältnis von Femme fatale und Femme fragile - Fuhry, Natalia (70 Jahre Germanistik in Zadar: Rückblicke, Einblicke, Ausblicke, 2026)
When examining Thomas Mann’s early works, it must be noted that female characters often play a secondary role, moving primarily within the tension between two stereotypes that flourished during the Fin de Siècle: the femme fatale and the femme fragile. Whether Gerda von Rinnlingen (The Little Herr Friedemann), Anna Jacoby (Luischen), or Gabriele Klöterjahn (Tristan), Thomas Mann’s early female characters are characterized by corresponding stereotypical attributes such as eroticism, demonization, idealization, death, and illness. In this regard, Thomas Mann may be regarded as a representative author of his time, an era in which conceptions of femininity were undergoing profound transformations, both in literature and in the socio-political sphere. The European fin de siècle period was profoundly influenced by the first wave of the women’s movement, during which assertive and self-assured female activists emerged in the public sphere, decisively challenging traditional conceptions of womanhood and destabilizing longestablished ideals such as the idyll of the bourgeois family. The following study seeks to explore to what extent interconnections can be discerned between the socio-political developments of the fin de siècle and the representation of female characters in Mann’s early works. It aims to determine whether Mann’s female characters merely reaffirm conventional stereotypes of femininity or whether they already exhibit elements of a deconstruction within the texts.